Associations between Sleep Duration, Sleep Quality, and Cognitive Test Performance among Older Adults from Six Middle Income Countries: Results from the Study on Global Ageing and Adult Health (SAGE) - Gildner, Theresa E. (American Academy of Sleep Medicine, 2014)
BACKGROUND: Alterations in sleep architecture are common among older adults. Previous studies have documented associations between sleep duration, sleep quality, and cognitive performance in older individuals, yet few studies have examined these trends using population-based samples from non-Western societies. The present cross-sectional study uses nationally representative datasets from six countries to test several hypotheses related to sleep patterns and cognitive function. METHODS: Data were drawn from the first wave of the World Health Organization's study on global ageing and adult health (SAGE), a longitudinal study using samples of older adults (≥ 50 years old) in 6 middle-income countries (China, Ghana, India, Russian Federation, South Africa, and Mexico). Self-report data provided information on sleep quality and sleep duration over the previous 2 nights, and 5 cognitive tests (immediate and delayed verbal recall, forward and backward digit span, and verbal fluency) were used to create a composite z-score of cognitive performance. RESULTS: Individuals with intermediate sleep durations (> 6-9 h/night) exhibited significantly higher cognitive scores than individuals with short sleep (0-6 h/night; p < 0.001) or long sleep duration (> 9 h/night; p < 0.001). Self-reported sleep quality was positively correlated with cognitive z-score (p < 0.05). Significant sex differences were observed; men generally had higher sleep quality and cognitive scores, while women reported longer sleep durations. DISCUSSION: This study documented positive correlations between cognitive scores and sleep quality, and between cognitive z-scores and intermediate sleep duration. These findings are clinically important given the growing rates of dementia and aging populations globally. CITATION: Gildner TE, Liebert MA, Kowal P, Chatterji S, Snodgrass JJ. Associations between sleep duration, sleep quality, and cognitive test performance among older adults from six middle income countries: results from the study on global ageing and adult health (SAGE). J Clin Sleep Med 2014;10(6):613-621.